Political Communication Dysfunction: The Impact of Controversial Statements by Public Officials on Public Trust - M. Yusril Juliansah; Oman Sukmana (Journal of Legal, Political, and Humanistic Inquiry, 2026)
The increasing prevalence of controversial statements by Indonesian public officials during the 2024–2025 period has generated public criticism and raised concerns regarding declining trust in government institutions. This study aims to analyze the relationship between political communication dysfunction and public trust erosion by examining the characteristics of controversial statements, digital media amplification mechanisms, and their implications for democratic governance. This research employs a qualitative normative library research approach based on documentary analysis of official statements, government documents, public trust reports, academic literature, and credible media sources. The analysis integrates Political Communication Theory, the OECD Framework on Drivers of Trust in Public Institutions, Aristotle’s Rhetorical Theory, Castells’ Communication Power Theory, and Coombs’ Situational Crisis Communication Theory. The findings reveal that controversial statements represent systemic communication dysfunction rather than isolated individual failures, affecting public trust dimensions, particularly integrity, responsiveness, and fairness. Digital media accelerates the spread of negative narratives through agenda-setting, framing, and echo chamber mechanisms, while ineffective crisis responses further weaken institutional credibility. The study concludes that strengthening communication accountability, digital literacy, empathetic leadership, and institutional crisis communication mechanisms is essential for restoring public trust and supporting democratic governance in Indonesia’s digital era.